FIRM VALUE: AUTOMOTIVE INDUSTRY RESEARCH - Murviana Koto; Angga Bayu Putra Wansa (Journal of International Conference Proceedings (JICP), 2019)
The automotive industry and its components growth the manufacturing sector in Indonesia. This industry creates many jobs and drives various other industries. The research aims to analyze the firm value of automotive companies based on capital structure and sales growth. The population of this research is the automotive company and its components listed on the Indonesia Stock Exchange. The sample was taken using a purposive sampling method, and the data was proceed using multiple linear regression analysis methods. The results showed that the capital structure had a negative effect on firm value using debt to equity ratio (DER), and had a positive effect using long-term debt to equity ratio (LDER). While sales growth has a non-significant positive effect on the firm value of automotive companies.